Audit committees and internal auditors in Malaysia - Puat Nelson, Sherliza; Devi, S. Susela (2007)
Audit committee is becoming increasingly important because it helps the stakeholders to constrain the behaviour of corporate managers. With the assistance that they receive from internal auditors, activities of the audit committees and internal auditors are now seen as critical elements in the assurance process. The interaction between these two parties is believed to be an important element in the corporate governance and control process. Thus the existing study intends to explore the interaction between the audit committees and their internal auditors.The objective of the paper is to explore if there are any associations in the relationship on the existence of direct communication of the working relationship between audit committee (AC) and internal auditor (CAE). Hence, we would like to explore that when the CAE has direct communication with AC such as CAE reports directly to AC and CAE has private meetings with AC; is there an association that (a) AC is responsible for the appointment of CAE, determines remuneration, and department’s budget, and (b) AC periodically approves and evaluates the audit plan, the performance, independence, scope and activities of the internal and external auditors? Mailed questionnaires were used as research instruments and were sent to audit committees and internal auditors working or attached to companies in Kuala Lumpur and Selangor (Malaysia). It was found that reporting directly to AC and having private meetings with AC had shown different results. The study is limited to the interaction between audit committees and internal auditors, especially on the type of communication where the internal auditors report directly (whether verbally or written) to the audit committees, and the private meetings they have. For future research it may be suggested that the mode of interaction between the two parties could be expanded.